Competence of Technical Workers in Industrial Parks, Export Processing Zones, and High Tech Parks in Ho Chi Minh City - Thái Bá Cần; Đỗ Mạnh Cường (Journal of Technical Education Science, 2006)
Competency of the workers is an important one among the aspects of human resource quality. As required by Hepza, IPE-HCMUTE (Institute for Research and Development of Professional Education) conducted a research to evaluate the quality of workforce in Industrial Parks, Export Processing Zones, and High Tech Park in Ho Chi Minh city. This article presents the evaluations of managers about workforce competencies.